Analysis of Production Technician Satisfaction Towards Training Service Quality by Technical Training Department PT. ABC by Using Service Quality and Importance Performance Analysis - Gandi Suhartinah; Hery Hamdi Azwir (President University, 2018)
Department of technical training is the department that responsible for training program for the entire production technician in PT.ABC. In order to constantly improve the quality of training service, a research was conducted to analyze the satisfaction of production technician towards training service quality that organized by technical training department. Production technician will determine, whether the training program has been satisfactory or not. To determine the participants' satisfaction of the quality of the training service, this research has started by using the concept of service quality and also shows a model of service quality gap. Analysis of the participants' satisfaction was measured by using the service quality in order to know the gap between actual performance and expectation performance of the training service. This research was conducted to determine the priority factor that must be done to improve the quality of the training services. This factor is determined by using importance performance analysis method and the results from this research is customer satisfaction and priority factor for improvements which consists of the hygiene of training room, training content materials, training modules and clarity of training information.Keywords: Gap, Service Quality, Training, Expectations, Actual, Importance Performance Analysis